2019
DOI: 10.4103/ija.ija_782_18
|View full text |Cite
|
Sign up to set email alerts
|

The subcostal nerve as the target for nerve stimulator guided transverse abdominis plane blocks – A feasibility study

Abstract: Background and Aims: Transverse Abdominis Plane (TAP) block was originally described as a landmark-based technique. Peripheral nerve stimulator (PNS) guided blocks are still widely performed, where ultrasound is unavailable. Methods: Cadaveric dissections were performed which showed the subcostal nerve following a predictable course at the lateral abdominal wall in the TAP. The subcostal nerve was identified by ultrasound in three volunteers. Stimulation of the subcosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The subcostal nerve, the largest among the thoracic spinal nerves in diameter, travels below the 12th rib, passes behind the kidney, and gives rise to branches, including the lateral cutaneous nerve and the motor branch to pyramidalis [12]. The subcostal nerve, unlike the intercostal nerves, is especially susceptible to injury as it passes beyond the tips of intact ribs that could otherwise shield the nerve from damage.…”
Section: Introductionmentioning
confidence: 99%
“…The subcostal nerve, the largest among the thoracic spinal nerves in diameter, travels below the 12th rib, passes behind the kidney, and gives rise to branches, including the lateral cutaneous nerve and the motor branch to pyramidalis [12]. The subcostal nerve, unlike the intercostal nerves, is especially susceptible to injury as it passes beyond the tips of intact ribs that could otherwise shield the nerve from damage.…”
Section: Introductionmentioning
confidence: 99%
“…This journal has published in the past various original articles and reports pertaining to these newer blocks and their comparisons with older blocks. [234567891011121314] This issue of the journal reports a randomised trial wherein COMBIPECS (combinations of Pecs 1 and Pecs 2) block has been studied for breast surgeries. [15]…”
mentioning
confidence: 99%
“…Most of the studies related to fascial plane block are primarily related to the analgesic effect as the primary outcome measure. [2456789101112131415] The majority of the studies report that addition of these newer blocks decreases the requirement of analgesics (specifically opioid) during the perioperative period. The comparative study among individual blocks has reported variable results and the superiority of an individual block has not been determined conclusively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…have described in their study subcostal nerve stimulation–guided TAP block. [11] The relationship between the subcostal nerve and TAP was established by cadaveric dissections. Following sono-identification of the subcostal nerve in volunteers, the authors have conducted a feasibility study of subcostal nerve stimulation-guided TAP block in patients.…”
mentioning
confidence: 99%